Efektivitas Perekrutan Tenaga Kerja Lokal dari Perspektif Economic Analysis of Law - Partama Putra, I Wayan (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Based on the Badung Regency Regional Regulation Number 8 of 2014 concerning the Implementation of Employment Services in article 11 of the perda, it states that companies provide opportunities for local workers, with the company's needs without compromising labor competency standards. The theory of effectiveness is used to dissect and analyze aspects of the benefits of local labor recruitment with the theory of Economic Analysis of Law where the data obtained are data from field research. From the description above, two problems are obtained, related to the effectiveness of the Badung Regency Regional Regulation Number 8 of 2014 on the recruitment of local workers from the perspective of the Economic Analysis of Law and the inhibiting and supporting factors of the effectiveness of the Regional Regulations. The method in this research is empirical legal research, descriptive nature with the type of real behavior approach and statutory approach. Sources of data used are primary data and secondary data, data collection techniques by observation, interviews and documentation studies. Determination of the research sample used is positive sampling. The data analysis used is qualitative analysis. The recruitment of local workers to companies in the Kerobokan Traditional Village was declared effective because each company made sure that local workers were well absorbed. However, the ineffectiveness was found because the percentage of the agreement between the Kerobokan Traditional Village and the company was that 40% of the local workforce was not fulfilled.